Does corruption hinder trade for the new EU members? - Nicholas Horsewood; Anca Monika Voicu (Economics: The Open-Access, Open-Assessment E-Journal, 2012)
The paper uses a gravity trade model to examine the impact of corruption on bilateral trade using a data set comprising OECD economies, new EU members and developing nations. Although the level of corruption of both the importing and exporting nations does hinder cross-border transactions, differences between their ethical standards do have a negative impact on trade flows. The model is used to assess the impact on exports and imports of Romania and Bulgaria joining the European Union.
Keywords: C22; F10; F32; 330; trade; corruption; EU membership; Außenwirtschaft; Korruption; EU-Erweiterung; EU-Staaten (Osteuropa)